(untitled) (Global Journal of Human-Social Science, 2024)
This article proposes a typology of Jamaican immigrant organizations in Toronto Canada and examines the circumstances shaping the establishment of immigrant organizations with diverse orientations within this immigrant group This analysis is informed by archival research that involved the examination of Caribbean newspapers including The Share Contrast and The Islander that published articles about events and concerns particular to Caribbean communities in Toronto Canada between 1960 and 2005 Information about the number and types of organizations established by Jamaican immigrants was obtained through a combination of internet research and information from the Consulate Generals Office of Jamaican in Toronto Canada The research shows that Jamaican immigrants have established more than 80 organizations of various types namely sociocultural political ethnic alumni and special interest organizations Additionally the research asserts that there are ethno-specific and social spatial factors that contributed to the establishment of these organizations Specifically the desire to encourage sense of belonging in the place of residence through the celebration of events particular to their identity increasing ethnic diversity within the group and changes in the availability of settlement assistance for immigrants in Toronto are factors that contributed to the establishment of diverse Jamaican immigrant organizations